EDUKASI PEMANFAATAN LIMBAH KULIT SALAK MENJADI TEH HERBAL KEPADA ANGGOTA PKK DESA BANJAR SEMINAI - Edo Arribe; Syahvi Ramadhan; Yoga Surya Agustion; Vhany Syafri Andini; Edwi Ferlanda (Jurnal AbdiMas Nusa Mandiri, 2026)
Banjar Seminai Village, located in Dayun District, Siak Regency, is the largest producer of snake fruit, with production reaching 8,403.92 quintals in 2024. This large production volume has led to an increase in snake fruit peel waste, but it has not been optimally utilized yet. This problem give a potentially polluting the environment and miss economic opportunities for the community. The purpose of this community service activity is to educate on utilizing snake fruit peel waste into a valuable product in the form of herbal tea. The approach employed is Asset-Based Community Development (ABCD) with the stages of village asset identification, outreach, participatory discussions, and demonstrations of herbal tea making. This activity was attended by the Banjar Seminai Village community, including snake fruit farmers, housewives, and village youth. The activity's outcomes demonstrated a growth in the community's knowledge and awareness on regarding snake fruit peel waste management, as evidenced by the active participation of participants during the discussion and their interest in trying to process snake fruit peel waste independently. The community also expressed their interest in developing businesses based on local products. The end result of this activity is that utilizing salak peel waste to make herbal tea it’s not only increases environmental awareness but also creates a new economic opportunities for the community. This activity aims to serve as the initial phase in creating sustainable, high-quality village products and boosting the local economy.